Sex differences on patient safety culture practices among nurses in Karawang, Indonesia: a cross-sectional study - Lilis Suryani; Santhna Letchmi; Faridah Mohd Said (Intelektual Pustaka Media Utama, 2026)
Nurses are critical in enhancing the quality of care and patient safety due to their commitment to caring for patients 24 hours a day and their interaction with families and other health professionals. The role of gender in the interprofessional team is more complex and warrants further investigation, even though it has been increasingly studied at the level of the individual healthcare provider. In this study, we examined sex differences in patient safety culture practices among nurses. This study was conducted using a cross-sectional design at a general public hospital in Karawang, West Java, Indonesia. The hospital survey on patient safety culture (HSPSC) was used. A chi-square test and an independent t-test were used to determine whether there were any differences in patient safety culture practice between the sexes. A total of 75 males and 145 females agreed to join this study. The mean age of female and male participants was 34.21 ± 14.07 and 36.29 ± 12.51 years old, respectively. Age, marital status, and working position were significantly different between males and females (p < 0.05). Females reported to have a higher overall score of patient safety culture practices than males (3.65 (SD = 1.12 vs. 3.11 (SD = 1.43), p-value = 0.001). According to the patient safety culture practice domain, teamwork (4.21 (SD = 1.35) vs. 3.78 (SD = 1.76), p-value = 0.001), response to error (3.56 (SD = 1.93) vs. 3.31 (SD = 1.93), p-value = 0.001), and communication openness (3.881.56 vs. 2.35 (SD = 0.92), p-value = 0.001) were higher among female than male. Nurses must be trained, and professional communication must be improved as a means of ensuring better patient safety. Patient safety cultures vary widely across hospitals, units, and countries, as evidenced by the growing number of studies that have looked at this issue in depth.